Tuning of the photocatalytic 1,4-dioxane degradation with surface plasmon resonance of gold nanoparticles on titania - Min, Byoung Koun; Heo, Jung Eun; Youn, Na Kyoung; Joo, Oh Shim; Lee, Hyunjoo; Kim, Jin Hyung; Kim, Hoon Sik (ELSEVIER SCIENCE BV, 2009)
Gold nanoparticles supported on TiO(2) promoted the 1,4-dioxane photocatalytic degradation. This beneficial effect of gold was found to originate from its surface plasmon resonance of which the magnitude is sensitive to both the density and the size of gold nanoparticles. Specifically, various Au-TiO(2) powders, which have a different number density and size of gold nanoparticles, were prepared by a leaching procedure. The highest photocatalytic activity of Au-TiO(2), which is almost two times higher than a commercial TiO(2), was attained at the optimum state of the density and size of gold nanoparticles where the maximum surface plasmon absorption was also obtained. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: TIO2; CATALYSIS; FILMS; SIZE; NANOCOMPOSITES; ABSORPTION; AU